REBT in the Treatment of Subclinical and Clinical Depression - Cândea, Diana (Best Practices in Cognitive-Behavioral Psychotherapy,, 2018)
The clinical protocols included in this book are focused both on clinical and subclinical depression and are targeted for both adults and youth. After providing a concise overview on depression and the empirical data supporting the clinical protocols, the book illustrates REBT/CBT protocols that provide essential guidance on how to address depression by practitioners at all levels of expertise (e.g. therapists in training and/or more experienced therapists). The field of psychotherapy research is now at a stage where the efficacy (i.e., how treatments work in controlled studies) and effectiveness (i.e., how treatments work in real life) of psychological treatments have been demonstrated for a large spectrum of disorders (Barlow, 2001). Cognitive - behavior therapies (CBT) are considered the gold standard for empirically validated forms of psychotherapy in the treatment of clinical and subclinical depression, showing short- and long-term effects (see Barlow, 2001; Chambless & Hollon, 1998) that are at least as strong as those of pharmacotherapy (medication) or other therapies (i.e., interpersonal therapy; DeRubeis et al., 200 5; Hollon et al., 2005; Shea et al., 1992) and it is hoped that these treatments will help not only treat but also prevent the onset of major depression (Cuijpers, Smit, & Straten, 2007). Cognitive -behavior therapies are based on the premise that psychological problems stem from dysfunctional cognitions (Beck, Rush, Shaw, & Emery, 1979; Ellis, 1962). In CBT, the therapist works with the client to identify and focus upon dysfunctional cognitions to modify them and remedy associated emotional and/or behavior al consequences. Two of the most influential and widespread forms of CBT are cognitive therapy (CT) and rational emotive behavior therapy (REBT) (Elis, 1987; David, 2007; David & Szentagotai, 2006). .